Testing Irrigated Cotton Production - J. Aguilar; R. S. Currie; D. Tomsicek; L. Haag; S. Duncan (Kansas Agricultural Experiment Station Research Reports, 2021)
Cotton research was initiated in Garden City, KS, which is the northern rim of the typical cotton production area. Initial results showed that with specific seed varieties and strategic irrigation management, cotton could be grown and provide decent yield in this region. There is still additional research that needs conducted, particularly with regards to germination and seeding rates.
Keywords: cotton; irrigation; thermo-limited cotton; irrigated cotton; southwest Kansas